Sentiment Analysis of Covid-19 Vaccination Policy in Indonesia - Ahmad Zaky; Retno Kusumastuti (Universitas Sebelas Maret, 2022)
In December 2020, the COVID-19 pandemic had lasted for 10 months in Indonesia and there was no way out of the pandemic. A glimmer of hope came from President Joko Widodo in August 2020 when he said that the vaccination program would start in January 2021 and the vaccine had arrived in Indonesia in December 2020. Various responses have emerged in the community regarding the vaccination policy, especially on social media. Public trust in a policy is one of the factors driving a successful policy. This article shows how the public's sentiment is towards the covid-19 vaccination policy by conducting text mining on netizen comments on YouTube social media, analyzes the sentiment from citizens, and analyzes the topics discussed about the covid-19 vaccination policy. The results showed that the majority of netizens had negative sentiments about the covid-19 vaccination policy with concerns, among others, about vaccine safety issues and the potential for corruption from the policy. To increase public confidence in the covid-19 vaccination policy, the government must answer them. Concerns about vaccine safety can be overcome by giving an example of a high government official of being willing to be vaccinated beforehand and live broadcast as was done by the elected president and vice president of the United States Joe Biden and Kamala Harris. Meanwhile, concerns over the potential for corruption can be resolved by taking more transparent, accountable and responsive actions in implementing the vaccination policy.